2018
DOI: 10.1167/18.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Serial dependence in the perception of visual variance

Abstract: The recent history of perceptual experience has been shown to influence subsequent perception. Classically, this dependence on perceptual history has been examined in sensory-adaptation paradigms, wherein prolonged exposure to a particular stimulus (e.g., a vertically oriented grating) produces changes in perception of subsequently presented stimuli (e.g., the tilt aftereffect). More recently, several studies have investigated the influence of shorter perceptual exposure with effects, referred to as serial dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
88
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 66 publications
13
88
2
1
Order By: Relevance
“…Particularly important for perceptual stability are attractive context effects which bias perception of the current sensory input towards recently encountered stimuli. Such effects have been reported in the auditory (Arzounian et al, 2017;Chambers et al, 2017) and visual modality (Cicchini et al, 2014(Cicchini et al, , 2017Fischer and Whitney, 2014;Manassi et al, 2017;Suárez-Pinilla et al, 2018), and have also been observed for the reproduction of single temporal intervals (Cicchini et al, 2012). Similar mechanisms are arguably at play during meter perception (London, 2004).…”
Section: Introductionsupporting
confidence: 64%
“…Particularly important for perceptual stability are attractive context effects which bias perception of the current sensory input towards recently encountered stimuli. Such effects have been reported in the auditory (Arzounian et al, 2017;Chambers et al, 2017) and visual modality (Cicchini et al, 2014(Cicchini et al, , 2017Fischer and Whitney, 2014;Manassi et al, 2017;Suárez-Pinilla et al, 2018), and have also been observed for the reproduction of single temporal intervals (Cicchini et al, 2012). Similar mechanisms are arguably at play during meter perception (London, 2004).…”
Section: Introductionsupporting
confidence: 64%
“…In a similar vein, serial dependence is often thought to arise on the level of objects (Liberman et al, 2014, suggesting that attention to a particular stimulus feature might not be necessary as long as the object is spatially attended. Conversely, one recent study showed that serial dependence in judgments about visual variance only occurred when observers attended and reported the variance of a previous motion stimulus and not its direction (Suárez-Pinilla et al, 2018). While this result calls the independence of serial dependence from feature-based attention into question, it is unclear whether this would generalize to perceptual decisions about lower-level visual features such as orientation or numerosity.…”
Section: Introductionmentioning
confidence: 93%
“…In line with this idea, recent studies have found that perceptual decisions about a large variety of visual stimulus features are biased towards features encountered in the recent past. Such features include orientation (Cicchini & Burr, 2017;Czoschke, Fischer, Beitner, Kaiser, & Bledowski, 2018;Fritsche et al, 2017), numerosity (Cicchini, Anobile, & Burr, 2014;Corbett, Fischer, & Whitney, 2011;Fornaciai & Park, 2018a), spatial location (Bliss, Sun, & D'Esposito, 2017;Manassi, Liberman, Kosovicheva, Zhang, & Whitney, 2018;Papadimitriou, White, & Snyder, 2016), visual variance (Suárez-Pinilla, Seth, & Roseboom, 2018), face identity (Liberman, Fischer, & Whitney, 2014), emotional expression and attractiveness (Xia, Leib, & Whitney, 2016). While it is still debated whether such serial dependence biases are introduced at a perceptual stage or at a post-perceptual, decision or short-term memory stage (Fritsche et al, 2017;Bliss et al, 2017;Cicchini & Burr, 2017;Fornaciai & Park, 2018a), the ubiquity of serial dependencies in perceptual decisions is striking and suggests that serial dependencies might arise from a general computation of the brain, potentially reflecting the stabilization of neural representations.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the timescale of repulsive adaptation are more variable. While some studies have found that adaptation in response to brief stimuli is short-lived, vanishing after a few seconds (Kanai and Verstraten, 2005;Patterson et al, 2013;Pavan et al, 2012), recent studies have reported minutes-long repulsive biases in perceptual decisions (Chopin and Mamassian, 2012;Gekas et al, 2019;Suárez-Pinilla et al, 2018). Together, these studies raise the possibility that attractive serial dependence and repulsive adaptation biases may occur over dissociable timescales.…”
Section: Introductionmentioning
confidence: 99%